2017
DOI: 10.18632/oncotarget.17792
|View full text |Cite
|
Sign up to set email alerts
|

IL13RA2 targeted alpha particle therapy against glioblastomas

Abstract: Glioblastoma (GBM) is the most aggressive primary malignant brain cancer that invariably results in a dismal prognosis. Chemotherapy and radiotherapy have not been completely effective as standard treatment options for patients due to recurrent disease. We and others have therefore developed molecular strategies to specifically target interleukin 13 receptor alpha 2 (IL13RA2), a GBM restricted receptor expressed abundantly on over 75% of GBM patients. In this work, we evaluated the potential of Pep-1L, a novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
60
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 43 publications
0
60
0
Order By: Relevance
“…However, it has been suggested that there is still an advantage to using the hybrid peptide for GB therapy in convection-enhanced delivery (CED), for which several clinical trials have been performed recently for the treatment of brain tumors (Mehta, Sonabend, & Bruce, 2017). One study reported on the efficacy of IL-13Rα2-targeted alpha therapy against GB using the Pep-1L peptide (Sattiraju et al, 2017), which was shown to target IL-13Rα2 by another group (Pandya, Gibo, Garg, Kridel, & Debinski, 2012). Several reports recently also showed evidence of cell-penetrating peptides crossing the blood-brain barrier (Gallo, Defaus, & Andreu, 2019;Stalmans et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been suggested that there is still an advantage to using the hybrid peptide for GB therapy in convection-enhanced delivery (CED), for which several clinical trials have been performed recently for the treatment of brain tumors (Mehta, Sonabend, & Bruce, 2017). One study reported on the efficacy of IL-13Rα2-targeted alpha therapy against GB using the Pep-1L peptide (Sattiraju et al, 2017), which was shown to target IL-13Rα2 by another group (Pandya, Gibo, Garg, Kridel, & Debinski, 2012). Several reports recently also showed evidence of cell-penetrating peptides crossing the blood-brain barrier (Gallo, Defaus, & Andreu, 2019;Stalmans et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The monomeric receptor interleukin‐13 receptor alpha 2 (IL‐13Rα2), which has a higher affinity to interleukin‐13 (IL‐13) than that of IL‐13Rα1 (Andrews, Holloway, Puddicombe, Holgate, & Davies, ), has significant roles in GB cells and can be used as a decoy receptor (Newman et al., ; Rahaman et al., ). Thus, several groups have reported the potency of targeting IL‐13Rα2 for GB therapy (Brown et al., ; Joshi, Husain, & Puri, ; Sattiraju et al., ; Sengupta, Thaci, Crawford, & Sampath, ; Thaci et al., ). We also reported the efficacy of targeting IL‐13Rα2 in GB cells with an immunotoxin, such as the cytotoxin IL‐13, in which receptor‐targeted human IL‐13 was fused with a mutated form of a Pseudomonas exotoxin (Kawakami, Kawakami, Liu, & Puri, ; Kawakami, Kawakami, & Puri, ; Kawakami, Kioi, Liu, Kawakami, & Puri, ).…”
Section: Introductionmentioning
confidence: 99%
“…These mice received 10 mg/kg 100 µL of the non-radioactive [ 19 F]DCP, 30 min prior to the injection of radiotracer. The images were reconstructed using TriFoil attenuation correction and Fourier rebinning parameters (56,66). The reconstructed CT and PET images were co-registered and analyzed using the TriFoil filtered backprojection 3D-OSEM algorithm.…”
Section: Optical Measurements and Data Analysismentioning
confidence: 99%
“…18 Cancer-specific receptors, such as the IL-13Rα2 or EGFRvIII receptors, which are specifically expressed or amplified glioblastomas, are already being tested for targeted therapies using ligand and aptamers, but are not yet widely available. [19][20][21] Here we aimed to adopt the hepatic ASGP-R/GN3 receptor/ligand system for targeted delivery of GN3conjugated ASOs to non-hepatic cancer cell lines, by ectopically expressing ASGP-R. Early work characterizing receptors in mouse fibroblasts, and more recent work in HEK293T cells, showed that ASGP-R is functional when expressed ectopically.…”
Section: Introductionmentioning
confidence: 99%